Efficient quantum dot-sensitized solar cell based on CdSxSe1-x/Mn-CdS/TiO2 nanotube array electrode. (20th January 2015) - Li, Zhen; Yu, Libo; Liu, Yingbo; Sun, Shuqing
Highlights: Translucent TiO2 nanotubes were used as substrate for QDSSCs. CdSx Se1-x /Mn-CdS QDs were sensitized onto TiO2 nanotubes by a two-stage strategy. The photoresponse of CdSx Se1-x /Mn-CdS/TiO2 nanotubes could be tuned with S/Se. Extra CdSe layers can improve the power conversion efficiency to 3.26%. Electrochemical measurements well evidenced the improved photovoltaic performance. Abstract: Translucent TiO2 nanotube (NT) array film has been used as supporter materials for the fabrication of CdSx Se1-x /Mn-CdS quantum dot sensitized solar cell (QDSSC). The TiO2 NT array electrodes are sensitized with Mn-CdS and CdSx Se1-x QDs by employing a two-stage sensitization strategy combining successive ionic layer adsorption and reaction (SILAR) techniques and hydrothermal process. The photoresponse region of CdSx Se1-x /Mn-CdS/TiO2 NT electrodes could be controlled by the ratio of S and Se. By systematical investigation the optimal composition of CdSx Se1-x, a high power conversion efficiency of 2.41% is obtained with CdS0.47 Se0.53 /Mn-CdS/TiO2 NT QDSSC prepared with feed molar ratio of S:Se = 0:4. After being coated with 3 SILAR cycles of CdSe on the CdS0.47 Se0.53 /Mn-CdS/TiO2 NT electrode, the power conversion efficiency could be further improved to the highest value of 3.26%. The enhancement of power conversion efficiency is mainly attributed to the significant increase of short-circuit current density ( J sc ) which resulted from the improved light harvesting ability caused by expanded light absorption range and efficient electrons collection caused by mid-gap states created by Mn-CdS. These results are well evidenced with the photovoltaic performance studies ( J - V behaviors), incident photon to charge carrier generation efficiency (IPCE), and electrochemical impedance spectroscopy (EIS).